Keabsahan Akta Perjanjian Pengikatan Jual Beli (PPJB) yang Objeknya Masih Dalam Sengketa di Pengadilan - Andi Hermawan; Endang Purwaningsih; Chandra Yusuf (Syntax Idea)
The notary makes a deed in the form of a PPJB deed based on a power of attorney agreement, which means that a legal relationship exists between the giver and the recipient of the power of attorney based on an agreement. The authority of a Notary to make an Authentic Deed comes from the provisions of Article 15 paragraph (1) UUJN. In order to avoid violations that could lead to Notarial actions that could be charged by criminal articles, Notaries in making Authentic Deeds, especially PPJB deeds, must always pay attention to the applicable legal rules. The formulation of the problem in this research is that regarding the position of the PPJB deed, it is known that the object is still in dispute in court and the legal consequences of the PPJB. This thesis uses normative legal research methods (library) with qualitative analysis of secondary data to obtain conclusions about the position of the PPJB deed, it is known that the object is still in dispute in court and is invalid because the legal act of buying and selling through the PPJB does not meet the requirements. the validity of the agreement regulated in Article 1320 of the Civil Code and the material requirements in making a PPJB deed. As a legal consequence of the PPJB deed, it is known that its object is still under dispute in court, namely that it is null and void and is not binding on the parties who made it. So, the achievements that have been made will return to normal. Apart from that, this results in the Notary being asked to take responsibility under UUJN and the code of ethics in making PPJB deeds where it is known that the object is still in dispute in court.